Preparation of sol-bonded lead zirconate titanate ceramics via sol-gel and mixed-oxide methods - Chontira Sangsubun (2018)
PZT ceramics were prepared from a mixture of a mixed-oxide powder with the particles as large as 1 m, and a sol from a triol sol-gel method. The latter provided small particles of ∼20-100 nm after being calcined at 600°C. This mixture thus so called 'sol-bonded PZT powder'. The powder was sintered at the temperature between 950-1200°C. X-ray diffraction results suggested that phases were changed from predominant rhombohedral to tetragonal with increasing the sintering temperature. The maximum room temperature dielectric constant of 1471 at 1 kHz could be achieved in the ceramic sintered at 1100°C, where the densification was optimized.